2022
DOI: 10.1101/2022.06.06.495021
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

UVC Inactivation of Black Mold is Wavelength-Dependent, and its Growth in HVAC Systems is Preventable Using Periodic Dosing with commercially available UVC LEDs

Abstract: Mold growth in HVAC systems poses a threat to human health, increases facility management operating costs due to decreased air flow efficiency, and damages buildings, impacting buildings' attractiveness in an ever more competitive property market concerned with both carbon footprint and ventilation quality. Although UVC treatment of HVAC systems has been shown to reduce growth, efficient design requires a specified amount of UVC dose coupled with a specific dosing strategy. UVC disinfection efficacy and wavele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 35 publications
0
1
0
Order By: Relevance
“…Sufficiently aggressive high-efficiency particulate air (HEPA) filters can trap some viral particles but create a significant pressure head (14), consuming more power, lowering flow and increasing noise. Mercury lamps that produce Ultraviolet subtype C (UVC) light have previously been used to disinfect and prevent mold and bacterial growth on HVAC coils, especially in buildings (15). Studies have also shown that a combination of Ultraviolet-A (UVA) and TiO2 can disinfect airborne bacteria and viruses (16).…”
Section: Introductionmentioning
confidence: 99%
“…Sufficiently aggressive high-efficiency particulate air (HEPA) filters can trap some viral particles but create a significant pressure head (14), consuming more power, lowering flow and increasing noise. Mercury lamps that produce Ultraviolet subtype C (UVC) light have previously been used to disinfect and prevent mold and bacterial growth on HVAC coils, especially in buildings (15). Studies have also shown that a combination of Ultraviolet-A (UVA) and TiO2 can disinfect airborne bacteria and viruses (16).…”
Section: Introductionmentioning
confidence: 99%